Polymer-free sirolimus-eluting stent use in Europe and Asia: Ethnic differences in demographics and clinical outcomes - Krackhardt, Florian; Waliszewski, Matthias; Wan Ahmad, Wan Azman; Kočka, Viktor; Toušek, Petr; Janek, Bronislav; Trenčan, Milan; Krajči, Peter; Lozano, Fernando; Garcia-San Roman, Koldobika; Otaegui Irurueta, Imanol; Garcia Del Blanco, Bruno; et al. (PloS one, 2020)
BACKGROUND: The objective of this study was to assess regional and ethnic differences in an unselected patient population treated with polymer-free sirolimus-eluting stents (PF-SES) in Asia and Europe. METHODS: Two all-comers observational studies based on the same protocol (ClinicalTrials.gov Identifiers: NCT02629575 and NCT02905214) were combined for data analysis to assure sufficient statistical power. The primary endpoint was the accumulated target lesion revascularization (TLR) rate at 9-12 months. RESULTS: Of the total population of 7243 patients, 44.0% (3186) were recruited in the Mediterranean region and 32.0% (2317) in central Europe. The most prominent Asian region was South Korea (17.6%, 1274) followed by Malaysia (5.7%, 413). Major cardiovascular risk factors varied significantly across regions. The overall rates for accumulated TLR and MACE were low with 2.2% (140/6374) and 4.4% (279/6374), respectively. In ACS patients, there were no differences in terms of MACE, TLR, MI and accumulated mortality between the investigated regions. Moreover, dual antiplatelet therapy (DAPT) regimens were substantially longer in Asian countries even in patients with stable coronary artery disease as compared to those in Europe. CONCLUSIONS: PF-SES angioplasty is associated with low clinical event rates in all regions. Further reductions in clinical event rates seem to be associated with longer DAPT regimens.
Keywords: Coronary Artery Disease; nemoci koronárních tepen; Středomoří; Humans; Mediterranean Region; Drug-Eluting Stents; lidé středního věku; koronární angioplastika; Korejská republika; Malaysia; Malajsie; Female; Aged; Sirolimus; Ethnicity; sirolimus; senioři; lidé; Europe; infarkt myokardu; imunosupresiva; Republic of Korea; polymery; Immunosuppressive Agents; Polymers; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; Myocardial Infarction; prognóza; stenty uvolňující léky; incidence; Incidence; Percutaneous Coronary Intervention; etnicita; Prognosis; mužské pohlaví; prospektivní studie; Evropa; následné studie; Prospective Studies